Приключения веселых мышат: сказки / Елена Агинская - Агинская Елена Николаевна (Читаем сами, 2014)
Экземпляры: ф.6 (20151204) / Инвентарный номер: 52055 / Цена: 45.00. / Сис.шифр: Д / Авт.знак: А 24 / ГРНТИ: 17.82.93 / ББК: 84(2Рос-Рус)